Nanocoating and biological evaluation of clindamycin- and rifampicin-loaded nanospheres impregnated silicone tube for antibacterial application - Watunyu Thanongsak (2022)
Two types of nanospheres, namely clindamycin-loaded nanospheres (CN) and rifampicin-loaded nanospheres (RN) were successfully prepared using emulsion solvent evaporation technique. Poly(ε-caprolactone-random-d,l-lactide)-block-poly(ethylene glycol)-block-poly(ε-caprolactone-random-d,l-lactide) (PLEC) was used for preparing nanospheres. CN and RN were coated on an antibiotic-impregnated silicone tube surface by spray coating technique. The formulations of antibiotic-loaded nanospheres (CN and RN) and the amount of spray coating cycles were optimized. Drug-loading content (DLC), encapsulation efficiency, zeta potential, and size of nanospheres were characterized. The optimal ratios of PLEC to clindamycin; and PLEC to rifampicin were both at 2:1. Drug-loading contents of CN and RN were 2.62 ± 0.04% and 7.02 ± 0.02%, respectively. The optimum coating of 90 cycles was provided DLCs of 0.0637 ± 0.033 wt.% and 0.0613 ± 0.018 wt.% for rifampicin and clindamycin, respectively. The coating of silicone tube was able to prolong the release of both antibiotics for at least 30 days. Antibacterial activity test was performed using MRSA (ATCC 43300) and S. Epidermidis (ATCC 12228). Moreover, the cytotoxicity of antibiotic-loaded nanospheres coated on silicone tubes was evaluated. The coated silicone tube showed antibacterial activity for at least 28 days and was biocompatible with L929 cells.